1982
DOI: 10.1073/pnas.79.7.2255
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational modification and processing of Escherichia coli prolipoprotein in vitro.

Abstract: These results indicate that our in vitro system contains activities of prolipoprotein modification and processing enzymes, including glyceryltransferase, O-acyltransferase, signal peptidase, and N-acyltransferase. The signal peptidase activity in our in vitro system was completely inhibited by globomycin. At pH 5.0, glyceryltransferase was inactive. Signal peptidase was active at pH 5.0, provided that prolipoprotein had been modified by glyceryltransferase (and O-acyltransferase) during a prior incubation at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
142
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(144 citation statements)
references
References 31 publications
0
142
0
1
Order By: Relevance
“…1B) (22). In Gram-negative bacteria, the N-terminal cysteine residue of Braun's murein lipoprotein (23) is modified by N-acyltransferase (Lnt), yielding mature N-acylated lipoprotein (20). Bursa aurealis insertions in lgt and lsp were identified in the Phoenix library; however, bioinformatic analysis revealed that lnt is not present in the genome of S. aureus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B) (22). In Gram-negative bacteria, the N-terminal cysteine residue of Braun's murein lipoprotein (23) is modified by N-acyltransferase (Lnt), yielding mature N-acylated lipoprotein (20). Bursa aurealis insertions in lgt and lsp were identified in the Phoenix library; however, bioinformatic analysis revealed that lnt is not present in the genome of S. aureus.…”
Section: Resultsmentioning
confidence: 99%
“…Lipoproteins are synthesized in the cytoplasm as precursors with an N-terminal signal peptide for secretion via the Sec pathway (18,19). Lipoprotein diacylglycerol transferase (Lgt) catalyzes transfer of phosphatidylglycerol to the sulfhydryl moiety of a cysteine residue conserved in the signal peptides of all lipoprotein precursors (20,21). The product of this reaction is then cleaved at the modified cysteine by lipoprotein (type II) signal peptidase (Lsp) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The prolipoprotein undergoes a series of modification and processing reactions to become the mature free-form lipoprotein, one third of which is covalently attached to the peptidoglycan [2]. Lipid modification of the prolipoprotein is a multi-step process; the first step is the transfer of the glyceryl moiety from phosphatidylglycerol to the cysteine residue in the unmodified prolipoprotein by prolipoprotein glyceryl transferzs~ [3].…”
Section: Introductionmentioning
confidence: 99%
“…2B. It has been shown that modification by glyceride of the cysteine residue that becomes the NHz-terminus of LP is a prerequisite for the signal peptide cleavage [2,4,5]. To confirm this the unmodified pro-LP-containing envelope was used as substrate.…”
Section: Substrate Specificitymentioning
confidence: 99%
“…The cell envelope of Escherichia coli contains several species of the lipoproteins that are first synthesized in a glyceride-containing percursor form with a signal peptide at the NHz-terminus [2,3] and then converted to a mature form [4,5]. These in-+ To whom correspondence should be addressed Abbreviations: LP, major outer membrane lipoprotein; PAL, peptidoglycan-associated lipoprotein; NLP, new lipoprotein; pro-LP, pro-PAL, and pro-NLP, glyceridecontaining precursors of LP, PAL and NLPs, respectively; SDS, sodium dodecyl sulfate elude the major outer membrane lipoprotein (LP), the peptidoglycan-associated lipoprotein (PAL) and additional lipoproteins (NLPs) that have been found only recently.…”
Section: Introductionmentioning
confidence: 99%